Burkholderia cepacia outbreak in immunocompetent children in a tertiary hospital in Turkey: A case series - Ceren Cetin; Ugurgul Arslan (Asian Pacific Journal of Tropical Medicine, 2022)
Objective: To report an outbreak of Burkholderia (B.) cepacia related to contaminated surface cleaner in the pediatric ward of a tertiary hospital in Turkey. Methods: This study retrospectively reported the outbreak occurred between January 16, 2018 and January 23, 2018. Twelve immunocompetent patients who developed a bloodstream infection a few days after the hospitalization and who were positive for B. cepacia were included. Environmental samples were collected from various areas in the hospital to find the source of the outbreak. Results: All patients had clinical and biochemical evidence of sepsis. None of the patients had an underlying disease or had a central venous catheter as a risk factor. B. cepacia was isolated from the samples taken from the surface cleaners. The antibiotic susceptibilities of B. cepacia isolates were identical in the surface cleaners with the isolates from the patients’ blood cultures. The outbreak was controlled after removing the surface cleaners from use. None of the infected patients died during the outbreak. Conclusions: Nosocomial B. cepacia outbreak may occur in immunocompetent children as well. Rapid identification of the outbreak, defining the source and taking appropriate measures to control the outbreak are the key points in the management.